Water, time and a dark-green coat. On Chopin’s Barcarolle - Czaja, Dariusz (Interdisciplinary Studies in Musicology, 2018)
The Barcarolle, Op. 60 is a late (1846) Chopin masterpiece. The shrewdest interpreters (Maurice Ravel, Jarosław Iwaszkiewicz) immediately understood that this miniature represents something much deeper than just a skilful stylisation based on Italian (Venetian?) melody. The author presents and discusses in detail several hermeneutic attempts at interpreting the meanings of the Barcarolle, devoting particular attention to Iwaszkiewicz’s sketch ‘Barkarola Chopina’. He also draws attention to the peculiar rhetoric of the text (strongly marked aquatic motifs, accentuated polyvalence and the shimmering of meaning). He goes on to reveal striking connections between the semantics of Iwaszkiewicz’s essay on the Barcarolle and his texts devoted to Venice. In the final section, he puts forward the hypothesis that the Barcarolle can be interpreted as a musical portrait of Venice - a portrait made of sounds, and so by definition vague, allusive and symbolic; a portrait in which the rocking and shimmering of the notes is also the shimmering of meaning.